Alligators in the abyss: The first experimental reptilian food fall in the deep ocean. - Craig Robert McClain; Clifton Nunnally; River Dixon; Greg W Rouse; Mark Benfield (PLoS ONE)
The high respiration rates of the deep-sea benthos cannot be sustained by known carbon supply pathways alone. Here, we investigate moderately-sized reptilian food falls as a potential alternative carbon pathway. Specifically, three individual carcasses of Alligator mississippiensis were deployed along the continental slope of the northern Gulf of Mexico at depths of ~2000m in early 2019. We posit the tough hide of alligators would impeded scavengers by limiting access to soft tissues of the alligator fall. However, the scavengers began consuming the food fall 43 hours post-deployment for one individual (198.2cm, 29.7kg), and the carcass of another individual (175.3 cm, 19.5kg) was completely devoid of soft tissue at 51 days post-deployment. A third individual (172.7cm, 18.5kg) was missing completely after 8 days, with only the deployment harness and weight remaining drug 8 meters away, suggesting a large elasmobranch scavenger. Additionally, bones recovered post-deployment reveal the first observations of the bone-eating Osedax in the Gulf of Mexico and are confirmed here as new to science. The findings of this study indicate the quick and successful utilization of terrestrial and aquatic-based carbon food sources in the deep marine environment, though outcome variability may be high.